Safety and efficacy of cipaglucosidase alfa plus miglustat versus alglucosidase alfa plus placebo in late-onset Pompe disease (PROPEL): an international, randomised, double-blind, parallel-group, phase 3 trial. Issue 12 (December 2021) - Schoser, Benedikt; Roberts, Mark; Byrne, Barry J; Sitaraman, Sheela; Jiang, Hai; Laforêt, Pascal; Toscano, Antonio; Castelli, Jeff; Díaz-Manera, Jordi; Goldman, Mitchell; van der Ploeg, Ans T; Bratkovic, Drago; et al.
Summary: Background: Pompe disease is a rare disorder characterised by progressive loss of muscle and respiratory function due to acid α-glucosidase deficiency. Enzyme replacement therapy with recombinant human acid α-glucosidase, alglucosidase alfa, is the first approved treatment for the disease, but some patients do not respond, and many do not show a sustained benefit. We aimed to assess the safety and efficacy of an investigational two-component therapy (cipaglucosidase alfa, a novel recombinant human acid α-glucosidase, plus miglustat, an enzyme stabiliser) for late-onset Pompe disease. Methods: We did a randomised, double-blind, parallel-group, phase 3 trial at 62 neuromuscular and metabolic medical centres in 24 countries in the Americas, Asia-Pacific, and Europe. Eligible participants were aged 18 years or older with late-onset Pompe disease, and had either been receiving alglucosidase alfa for at least 2 years or were enzyme replacement therapy-naive. Participants were randomly assigned (2:1) using interactive response technology software, stratified by 6-min walk distance and previous enzyme replacement therapy status, to intravenous cipaglucosidase alfa (20 mg/kg) plus oral miglustat or to intravenous alglucosidase alfa (20 mg/kg) plus oral placebo once every 2 weeks for 52 weeks. Patients, investigators, and outcome assessors were masked to treatment assignment. The primary endpoint was change from baseline to week 52 in 6-min walk distance, assessed using a mixed-effect model for repeated measures analysis for comparison of superiority in the intention-to-treat population (all patients who received at least one dose of study drug). This study is now complete and is registered with ClinicalTrials.gov, NCT03729362 . Findings: Between Dec 3, 2018, and Nov 26, 2019, 130 patients were screened for eligibility and 125 were enrolled and randomly assigned to receive cipaglucosidase alfa plus miglustat (n=85) or alglucosidase alfa plus placebo (n=40). Two patients in the alglucosidase alfa plus placebo group did not receive any dose due to absence of genotype confirmation of late-onset Pompe disease and were excluded from analysis. Six patients discontinued (one in the alglucosidase alfa plus placebo group, five in the cipaglucosidase alfa plus miglustat group), and 117 completed the study. At week 52, mean change from baseline in 6-min walk distance was 20·8 m (SE 4·6) in the cipaglucosidase alfa plus miglustat group versus 7·2 m (6·6) in the alglucosidase alfa plus placebo group using last observation carried forward (between-group difference 13·6 m [95% CI −2·8 to 29·9]). 118 (96%) of 123 patients experienced at least one treatment-emergent adverse event during the study; the incidence was similar between the cipaglucosidase alfa plus miglustat group (n=81 [95%]) and the alglucosidase alfa plus placebo group (n=37 [97%]). The most frequently reported treatment-emergent adverse events were fall (25 [29%] patients in the cipaglucosidase alfa plus miglustat group vs 15 [39%] in the alglucosidase alfa plus placebo group), headache (20 [24%] vs 9 [24%]), nasopharyngitis (19 [22%] vs 3 [8%]), myalgia (14 [16%] vs 5 [13%]), and arthralgia (13 [15%]) vs 5 [13%]). 12 serious adverse events occurred in eight patients in the cipaglucosidase alfa plus miglustat group; only one event (anaphylaxis) was deemed related to study drug. One serious adverse event (stroke) occurred in the alglucosidase alfa plus placebo group, which was deemed unrelated to study drug. There were no deaths. Interpretation: Cipaglucosidase alfa plus miglustat did not achieve statistical superiority to alglucosidase alfa plus placebo for improving 6-min walk distance in our overall population of patients with late-onset Pompe disease. Further studies should investigate the longer-term safety and efficacy of cipaglucosidase alfa plus miglustat and whether this investigational two-component therapy might provide benefits, particularly in respiratory function and in patients who have been receiving enzyme replacement therapy for more than 2 years, as suggested by our secondary and subgroup analyses. Funding: Amicus Therapeutics.